Effect of surface properties of copper-modified commercial titanium dioxide photocatalysts on hydrogen production through photoreforming of alcohols. (23rd November 2017) - Clarizia, Laura; Vitiello, Giuseppe; Pallotti, Deborah Katia; Silvestri, Brigida; Nadagouda, Mallikarjuna; Lettieri, Stefano; Luciani, Giuseppina; Andreozzi, Roberto; Maddalena, Pasqualino; Marotta, Raffaele
Abstract: Deposition of copper on titanium dioxide holds great promise in producing materials with high activity in the photo-production of hydrogen by aqueous reforming of alcohols. This work aims at comparing hydrogen evolution through photoreforming of alcohols over photocatalysts prepared by in situ photodeposition of copper on three TiO2 commercial samples (P25, pure anatase, and pure rutile). The adoption of a single catalyst preparation method and experimental setup allowed to unequivocally ascribe the differences in hydrogen evolution to surface properties of the TiO2 sample tested, thus overcoming the major constraints found in the literature. The resulting samples were extensively characterized by several complementary techniques. Correlations between hydrogen production rates and physical-chemical properties of the samples are discussed. The analyses highlight the major role played by physical size and surface properties of TiO2 particles in determining the morphology, the dispersion of zero-valent copper nanoparticles on the TiO2 surface and, ultimately, the photocatalytic performances. Understanding the correlation between properties and photocatalytic response of copper-modified TiO2 nanoparticles acts as a remarkable lever for the future development of new TiO2 -based materials exhibiting high efficiency for hydrogen generation under UV–visible light irradiation. Graphical abstract: Highlights: Synthesis by in-situ photodeposition of Cu on commercial P25, anatase and rutile. Comparison of H2 production rates of bare TiO2 and Cu-modified TiO2 photocatalysts. Photocatalyst characterization by XRD, EDX, PL, FT-IR, DRUV, HR-TEM and FE-SEM. Assay of the TiO2 surface features affecting Cu deposition.